2006
DOI: 10.1681/asn.2005060627
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Association of Kidney Function with Valvular and Annular Calcification

Abstract: Valvular calcification is common in the setting of end-stage kidney disease and is associated with increased risks for cardiovascular disease events. It is unknown whether the prevalence of valvular calcification is increased in milder kidney disease after accounting for cardiovascular risk factors. Participants who attended the sixth examination of the Framingham Offspring Study (1995 to 1998) were eligible. Kidney function was estimated by GFR using the simplified Modification of Diet in Renal Disease Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(88 citation statements)
references
References 48 publications
4
81
1
2
Order By: Relevance
“…In the clinical course of chronic kidney disease, heart valve calcification can be seen even before initiation of HD. 27,28 The results in MultiEthnic Study of Atherosclerosis showed the prevalence of AVC was higher than that of MVC in patients with chronic kidney disease not requiring HD. 28 In our patients with mean HD duration of 95 months, the prevalence of AVC and MVC was 75.0 and 51.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical course of chronic kidney disease, heart valve calcification can be seen even before initiation of HD. 27,28 The results in MultiEthnic Study of Atherosclerosis showed the prevalence of AVC was higher than that of MVC in patients with chronic kidney disease not requiring HD. 28 In our patients with mean HD duration of 95 months, the prevalence of AVC and MVC was 75.0 and 51.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, end-stage renal disease has long been known to be a risk factor for the presence and progression of aortic stenosis, 40,41 though mild to moderate renal disease does not appear to be significantly associated with aortic valve calcification. 42 One study recently has identified metabolic syndrome as an additional risk factor for valve calcification. 43 The similarities between risk factors for atherosclerosis and calcific aortic valve disease have led to the hypothesis that calcific aortic valve disease is primarily a manifestation of atherosclerosis.…”
Section: Epidemiologymentioning
confidence: 99%
“…In the study of Sharma et al MVC predicted all-cause mortality, cardiovascular mortality and morbidity in ESRD patients [4]. MVC is common in the setting of ESRD [6,11,15,16] and in patients with chronic kidney disease before the onset of ESRD [17]. More recently, Fox et al have demonstrated that in the community, chronic kidney disease is associated with MVC before the onset of ESRD [17].…”
Section: Discussionmentioning
confidence: 99%